Cultura e tradição: os saberes e fazeres sobre os benzimentos na Comunidade Kalunga Vão de Almas/Cavalcante-GO - Pereira, Sulene Francisco (Universidade Federal do Tocantins, 2024)
This research aims to describe the traditional knowledge present in the tradition of blessing, a daily practice and present in the religious rites of the Kalunga. The context of the work is the Kalunga Community of Vai de Almas - GO. The interest in the study arose from reflection on this tradition, in view of the researcher's experience as a member of the community. The research methodology is based on ethnography, using observation, field research, interviews and a workshop aimed at elementary school students. The research highlights the relevance of the knowledge present in the quilombola tradition and its role in strengthening the local cultural identity.